Preservasi Dan Konservasi Sebagai Upaya Pustakawan Mempertahankan Koleksi Bahan Pustaka - Isran Elnadi (UIN Mataram, 2021)
The maintenance and preservation of library materials is carried out with the aim of preserving the information values ??contained in a document, accelerating information retrieval, maintaining the beauty and tidiness of documents, maintaining library materials so that they can still be used, and preventing collections from various factors that are damaging. The method used in writing this article is a literature study, with an emphasis on peeling, summarizing and collecting literature, then giving the analysis. Maintenance and preservation are carried out in the library, namely, 1) cleaning the collection from dust, 2) cleaning the floor every day, 3) avoiding using thick bookmarks, 3) holding both sides of the book while reading, 4) storing books in a dry place, 5) weeding the collection, 6) changing the shape using media, 7) reproduction of library materials, 8) binding and laminating. The factors that causing damages to library materials are, 1) physical factors or material characteristics, 2) environmental or climatic factors, 3) human factors. Activities and preservation of library materials required reliable human resources. Constraints in the preservation of library materials, namely, the lack of preservation personnel, the absence of institutions that handle it specifically and lack of funds.